LDL-aferéza v léčbě familiárních hyperlipoproteinemií - Bláha, Vladimír; Bláha, Milan; Lánská, Miriam; Havel, Eduard; Vyroubal, Pavel; Zadák, Zdeněk; Žák, Pavel; Sobotka, Luboš (Vnitrni lekarstvi, 2014)
LDL-apheresis is an extracorporeal elimination technique, which specifically removes LDL-cholesterol from the circulation. There are six methods for the selective LDL-cholesterol removal these days. The main indications for LDL-apheresis are the diagnosis of homozygous familial hypercholesterolemia, heterozygous familial hypercholesterolemia which is refractory the standard care and intolerance of routine care, and also patients with lipoprotein(a) increase resistant to the farmacotherapy. There is still debate which LDL-cholesterolemia is indication for LDL-apheresis therapy, and the recommendation differs among various countries. Despite large randomized trials are missing, there are several good quality studies to conclude, that the beneficial cardiovascular effects of LDL-apheresis in severe hypercholesterolemia are important and beneficial.
Keywords: triglyceridy; Blood Component Removal; Humans; Triglycerides; lidé; separace krevních složek; Hyperlipoproteinemia Type II; LDL-cholesterol; hyperlipoproteinemie typ II; Cholesterol, LDL; HDL-cholesterol; Cholesterol, HDL